2009
DOI: 10.1002/jsfa.3822
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sudan IV in hot chilli powder with luminol/dissolved oxygen chemiluminescence system

Abstract: The proposed method was successfully applied to the determination of Sudan IV in contaminated hot chilli powder, with recoveries ranging from 89.3 to 108.4%. The possible mechanism of enhancement of the luminol/dissolved oxygen CL reaction by Sudan IV can be attributed to the acceleration of electron transfer. Compared with other procedures, the proposed CL method offers the highest sensitivity and the least reagent consumption for the determination of Sudan IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…1)), an azo compound, is a non-ionic fat-soluble dye. They are extensively used in coloring waxes, oils, petroleum, solvents, and polishes (Niu, Song, & Chen, 2010;Xu, Heinze, Chen, Cerniglia, & Chen, 2007). It has also been used to enhance the appearance of products such as chilly, tomato sauces, salami, olive oil and many other frequently eaten foodstuffs (Baggiani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1)), an azo compound, is a non-ionic fat-soluble dye. They are extensively used in coloring waxes, oils, petroleum, solvents, and polishes (Niu, Song, & Chen, 2010;Xu, Heinze, Chen, Cerniglia, & Chen, 2007). It has also been used to enhance the appearance of products such as chilly, tomato sauces, salami, olive oil and many other frequently eaten foodstuffs (Baggiani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Flow injection (FI) analysis combined with CL, FI-CL, which possess merits of low limit of detection (LOD), fast response time, less reagent consumption, and simple instrumentation as well as automation, has become a very useful analytical tool in different scientific fields from food safety [3335] to environmental chemistry [3638]. In this work, it was found that UA could obviously quench the CL intensity of luminol-Co 2+ in a flow system, with the decrements in CL intensity linearly proportional to the logarithm of UA concentrations ranging from 3.0 to 500.0 nmol L −1 , giving the LOD of 1.0 nmol L −1 (3 σ ).…”
Section: Introductionmentioning
confidence: 99%
“…The simple and green CL system of luminol-dissolved oxygen has been applied for the determination of vitamin B 12 [18], sudan IV [19] and chlorogenic acid [20] by our group. However, no CL method of luminol-dissolved oxygen system has been utilized for the determination of ROX to date.…”
Section: Introductionmentioning
confidence: 99%